The effects of peace and conflict resolution education on emotional intelligence, self-concept and conflict resolution skills - Gazioğlu, Gamze. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2008., 2008)
The aim of the present study was to understand the effects of neo-liberal economies and globalization on education policies where they create inequalities and conflicts. However, the main goal of education was defined as a radical democratization in the schools through the transformation of knowledge. Curriculum plays important role in the transformation of knowledge and it is crucial to build a radical transformation of the societies. From this perspective, three alternative curricula namely; Peace Education (developed by the Education department of Harvard with the name Program for Young Negotiators), Conflict Resolution Education (developed by the International Center for Cooperation and Conflict Resolution, Teachers College at Columbia University), and Peace Education and Conflict Resolution Education combined were implemented and evaluated. The present study was to investigate the effects of these three curricula and to find the most effective curriculum among them on conflict resolution skills. The sample consisted of 330 students from the faculty of education from four different departments, namely Counseling and Guidance, English Language Teaching, Turkish Language Teaching and Mathematics Teaching at one of the universities in Istanbul. All were from families with moderate socio-economic levels. For data collection, the “Demographic Information Form”, and the Turkish forms of “Bar-On Emotional Quotient Inventory”, “Tennessee Self Concept Scale” and Conflict Resolution Scale were used. The findings indicated that the Peace Education, Conflict Resolution Education, and the Peace Education and the Conflict Resolution Education combined had significant effects on Emotional Intelligence, Self Concept and Conflict Resolution Skills. Among these three curricula, the Peace Education and Conflict Resolution Education combined had the highest effects on Emotional Intelligence, Self Concept and Conflict Resolution Skills where the second curriculum was the Peace Education which was more effective than the Conflict Resolution Education. The factors that additively and uniquely affected conflict resolution skills were also analyzed and it was found that Emotional Intelligence and Self Concept additively explained approximately 99.3% of the conflict resolution skills after the implementation of the three curricula. However, in this study, gender was not related to the conflict resolution skills.
Keywords: Self-perception.; Emotional intelligence.; Peace -- Study and teaching.; Conflict management -- Study and teaching.